Rapid evidence profile #40: What is known about mental-wellness challenges facing Canadians and mental health system-transformation initiatives? - DeMaio, P; Bhuiya, AR; Al-Khateeb, S; Wang, A; Khan, Z; El-Kadi, A; Sharma, K; Tchakerian, N; Alam, S; Bain, T; Song, X; Lavis, JN; et al. (My University, 2023)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about mental-wellness challenges facing Canadians and mental health system-transformation initiatives in response to a decision-maker’s request.
Keywords: mental wellness; Canadians; system; initiatives